Perspectives on Primary Blast Injury of the Brain: Translational Insights Into Non-inertial Low-Intensity Blast Injury - Siedhoff, Heather R.; Chen, Shanyan; Song, Hailong; Cui, Jiankun; Cernak, Ibolja; Cifu, David X.; DePalma, Ralph G.; Gu, Zezong (Frontiers in Neurology, 2022)
Most traumatic brain injuries (TBIs) during military deployment or training are clinically “mild” and frequently caused by non-impact blast exposures. Experimental models were developed to reproduce the biological consequences of high-intensity blasts causing moderate to severe brain injuries. However, the pathophysiological mechanisms of low-intensity blast (LIB)-induced neurological deficits have been understudied. This review provides perspectives on primary blast-induced mild TBI models and discusses translational aspects of LIB exposures as defined by standardized physical parameters including overpressure, impulse, and shock wave velocity. Our mouse LIB-exposure model, which reproduces deployment-related scenarios of open-field blast (OFB), caused neurobehavioral changes, including reduced exploratory activities, elevated anxiety-like levels, impaired nesting behavior, and compromised spatial reference learning and memory. These functional impairments associate with subcellular and ultrastructural neuropathological changes, such as myelinated axonal damage, synaptic alterations, and mitochondrial abnormalities occurring in the absence of gross- or cellular damage. Biochemically, we observed dysfunctional mitochondrial pathways that led to elevated oxidative stress, impaired fission-fusion dynamics, diminished mitophagy, decreased oxidative phosphorylation, and compensated cell respiration-relevant enzyme activity. LIB also induced increased levels of total tau, phosphorylated tau, and amyloid β peptide, suggesting initiation of signaling cascades leading to neurodegeneration. We also compare translational aspects of OFB findings to alternative blast injury models. By scoping relevant recent research findings, we provide recommendations for future preclinical studies to better reflect military-operational and clinical realities. Overall, better alignment of preclinical models with clinical observations and experience related to military injuries will facilitate development of more precise diagnosis, clinical evaluation, treatment, and rehabilitation.